2011
DOI: 10.1148/radiol.11101362
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of Multiple Sclerosis

Abstract: Owing to its ability to depict the pathologic features of multiple sclerosis (MS) in exquisite detail, conventional magnetic resonance (MR) imaging has become an established tool in the diagnosis of this disease and in monitoring its evolution. MR imaging has been formally included in the diagnostic work-up of patients who present with a clinically isolated syndrome suggestive of MS, and ad hoc diagnostic criteria have been proposed and are updated on a regular basis. In patients with established MS and in tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
182
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(193 citation statements)
references
References 195 publications
3
182
0
4
Order By: Relevance
“…Other MR techniques such as magnetization transfer, mean diffusivity, fractional anisotropy, perfusion, and MR spectroscopy have shown abnormalities in normal-appearing white matter in patients with MS. 30 Diffusion abnormalities are also seen in Alzheimer disease. 31 Maillard et al, 19 in a study of elderly subjects with cognitive health, cognitive impairment, and Alzheimer disease, showed an increased risk for white matter conversion to WMH in patients with lower fractional anisotropy and higher FLAIR signal in normal-appearing white matter.…”
Section: Discussionmentioning
confidence: 99%
“…Other MR techniques such as magnetization transfer, mean diffusivity, fractional anisotropy, perfusion, and MR spectroscopy have shown abnormalities in normal-appearing white matter in patients with MS. 30 Diffusion abnormalities are also seen in Alzheimer disease. 31 Maillard et al, 19 in a study of elderly subjects with cognitive health, cognitive impairment, and Alzheimer disease, showed an increased risk for white matter conversion to WMH in patients with lower fractional anisotropy and higher FLAIR signal in normal-appearing white matter.…”
Section: Discussionmentioning
confidence: 99%
“…MS patients are basically monitored by changes in clinical symptoms and by MR imaging, which detects lesions in the CNS but does not differentiate these lesions as inflammation, demyelination, or axonal damage (3). A noninvasive imaging technique such as PET could differentiate and quantify MS hallmarks and thus could be an important tool to monitor therapeutic response and help to better understand drug mechanisms.…”
mentioning
confidence: 99%
“…4,14 DTI is an advanced MR imaging technique that has been used in a number of in vivo and ex vivo studies. 15,16 DTI measures are able to identify alterations outside the focal lesions in the so-called normal-appearing white matter and normal-appearing gray matter that remain largely undetected with conventional MR imaging in patients with MS. 17 There is a growing interest in studying the DTI alterations of the SDGM in the different stages of the MS disease process. Previous studies suggested that SDGM DTI abnormalities are also present in patients with clinically isolated syndrome 18,19 and are associated with disability progression as well as cognitive dysfunctions in patients with MS. [20][21][22][23] Although different studies have investigated the associations between white matter lesions, brain atrophy, and DTI alteration in patients with MS, [24][25][26] the same relationships were not extensively investigated in healthy people whose pathophysiologic alteration of the brain cannot be attributable to the inflammatory process in the central nervous system.…”
mentioning
confidence: 99%